(untitled) (ELang | An English Language Education Journal, 2017)
This study is entilted “Improving Students’ Vocabulary Mastery by Using Flashcard”. In this research, the writer use flashcard as a media to increase students’ vocabulary mastery. the aims of the research are to know whether or not flashcard is effective to improve students’ vocabulary and also to know whether or not the students like being taught vocabulary by using flashcard. The design used in this research was pre-experimental. The subject of the research was the first grade students of Junior High School in Solokanjeruk 1. The researcher took one class as the sample which consist of 33 students. The data was obtained by conducting pretest, posttest and questionnaire. Pretest was given to know the scores before treatment, and the posttest score was given to know scores after treatment. The result of pretest and posttest scores was analyzed through the t-test formula to find out whether or not flashcard is effective. Based on computation result by using t-test formula, with df=N-1 =33-1 =32 at p=0.05 of two-tailed, the critical value of t is 2.042. the findings showed that t-obtained is higher than t-table (6.97 > 2.042). It indicated that the null hypothesis (H0) was rejected and the alternative hypothesis (Ha) was accepted. Based on the research findings, it can be concluded that flashcard is effective for improving students’ vocabulary mastery. futhermore, the results of questionnaires show that most students’ gave positive response toward the use of flashcard. Flashcard could improve students’ vocabulary mastery effectively, and they like being taught English vocabulary by it. Keywords: Vocabulary Mastery, Media, Flashcard